2020
DOI: 10.1186/s43141-020-00096-w
|View full text |Cite
|
Sign up to set email alerts
|

Activation of LacZ gene in Escherichia coli DH5α via α-complementation mechanism for β-galactosidase production and its biochemical characterizations

Abstract: Background Plasmid propagation in recombination strains such as Escherichia coli DH5α is regarded as a beneficial instrument for stable amplification of the DNA materials. Here, we show trans-conjugation of pGEM-T cloning vector (modified Promega PCR product cloning vector with tra genes, transposable element (Tn5)) and M13 sequence via α-complementation mechanism in order to activate β-d-galactosidase gene in DH5α strain (non-lactose-fermenting host). Results Trans-conjugation with pGEM-T allows correction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Inhibition% = 100 − Viability% a good enzymatic recovery of 73.96% being valuable for the industry in terms of economic point of view [23]. A. fumigatus L-methioninase was subjected under only two purification steps; which was better than those obtained for L-methioninase purification by Trichoderma harzianum [12], A. flavipes [24], Candida tropicalis [14], requires to three purification steps.…”
Section: Purification Of a Fumigatus L-methioninasementioning
confidence: 99%
“…Inhibition% = 100 − Viability% a good enzymatic recovery of 73.96% being valuable for the industry in terms of economic point of view [23]. A. fumigatus L-methioninase was subjected under only two purification steps; which was better than those obtained for L-methioninase purification by Trichoderma harzianum [12], A. flavipes [24], Candida tropicalis [14], requires to three purification steps.…”
Section: Purification Of a Fumigatus L-methioninasementioning
confidence: 99%
“…Mutagenesis using UV as a physical method for enhancement enzymes production from different fungal strains was studied by many workers in scientific field [27][28][29]. Fig ( 2) showed that UVmutagenesis play a critical role in alkaline cellulase production enhancement.…”
Section: Uv-mutagenesis For a Fumigatus Nrcf-122 Alkaline Cellulase Enhancemenmentioning
confidence: 99%
“…β-Galactosidase is a vital enzyme. The most extensively researched β-galactosidase (coded by the lacZ gene) is derived from Escherichia coli, which is widely used in the laboratory for DNA cloning, protein expression, and synthetic biology research (Hamed et al, 2020;Gao et al, 2021). The α-complementation phenomenon is a well-known feature of E. coli β-galactosidase (Ullmann et al, 1967).…”
Section: Introductionmentioning
confidence: 99%